Edukasi Cuci Tangan “Tepung Selaci Put-Put” Sebagai Upaya Pencegahan Penyakit Pada Santri TPQ di Kabupaten Temanggung - Mustain, Mukhamad; Wulansari, Wulansari; Dian Afriyani, Luvi (UNIVERSITAS NGUDI WALUYO, 2021)
Clean and Healthy Behavior (PHBS) is a reflection of a family's lifestyle that always pays attention to and maintains the health of all family members. Washing hands using soap and running water is one indicator of clean and healthy living behavior. Hand washing from WHO needs to be encouraged, which consists of washing hands in 6 steps by rubbing the palms, back of the hands, between the sidelines, locking movements, turning both thumbs and rotating fingertips that are easy to memorize with tepung selaci Put Put. Hand washing steps that are easy to memorize need to be taught at the age of children, including the TPQ Miftakhul Jannah students who are mostly followed by children aged students. The purpose of this activity is to increase the knowledge of the students about the importance of maintaining cleanliness and instilling a good handwashing culture from an early age. The method used is through lectures, games and hand washing demonstrations. The results of community service activities are the attitude/behavior of washing hands before education with a poor category as much as 57%, knowledge about hand washing before education which is in the sufficient category as much as 43% and the level of knowledge after education in the very good category as much as 48%. The conclusion is that education on hand washing with tepung selaci put put is able to increase knowledge about hand washing and suggestions are needed to monitor hand washing behavior regularly.ABSTRAKPerilaku Hidup Bersih Sehat (PHBS) merupakan cerminan pola hidup keluarga yang senantiasa memperhatikan dan menjaga kesehatan seluruh anggota keluarga. Cuci tangan menggunakan sabun dan air mengalir merupakan salah satu indikator perilaku hidup bersih dan sehat. Cuci tangan dari WHO perlu untuk digalakkan yaitu terdiri dari cuci tangan 6 langkah dengan langkah menggosok telapak tangan, punggung tangan, sela- sela, gerakan mengunci, putar kedua jempol dan putar ujung jari yang mudah dihafal dengan Tepung Selaci put put. Langkah cuci tangan yang mudah dihafal perlu diajarkan pada usia anak, tak terkecuali santri TPQ Miftakhul Jannah yang banyak diikuti oleh santri usia anak- anak. Tujuan kegiatan ini adalah peningkatan pengetahuan para santri tentang pentingnya menjaga kebersihan dan menanamkan budaya cuci tangan yang baik sejak dini. Metode yang digunakan melalui ceramah, permainan dan demonstrasi cuci tangan. Hasil kegiatan pengabdian masyarakat yaitu sikap/perilaku cuci tangan sebelum edukasi dengan kategori kurang baik sebanyak 57%, pengetahuan tentang cuci tangan sebelum edukasi yaitu kategori cukup sebanyak 43% dan tingkat pengetahuan setelah edukasi dengan kategori sangat baik sebanyak 48%. Kesimpulan yaitu edukasi cuci tangan tepung selaci put- put mampu meningkatan pengetahuan tentang cuci tangan dan saran diperlukan monitoring perilaku cuci tangan secara berkala.